Keputusan Pembelian Konsumen di Ritel Modern: Bukti Empiris dari Superindo Jawa Tengah - Dwi Syarifah Azzahra; Dian Marlina Verawati; Ipuk Widayanti (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The inconsistencies in previous research findings regarding the influence of promotions, product diversity, and price on purchasing decisions still raise questions, particularly because few studies have examined the context of modern supermarkets following the decline in offline shopping activity. Most studies have been conducted in metropolitan areas or online shopping channels, leaving little insight into consumer behavior at mid-tier supermarkets in non-metropolitan regions such as Central Java, where competition with traditional markets remains intense. To address this gap, this study aims to examine the contribution of these three factors while identifying the most dominant factor influencing Superindo customers’ purchasing decisions in Central Java. Using a quantitative approach, data were collected via an online questionnaire distributed to 180 respondents using purposive sampling. Analysis was performed using multiple linear regression with SPSS 22. The results indicate that price is the most dominant factor (t-calculated = 7.873; β = 0.478), followed by promotions (t = 5.220; β = 0.312), and product diversity (t = 5.201; β = 0.287). All three variables were found to have a positive and statistically significant partial effect. These findings confirm that a marketing strategy prioritizing competitive pricing, supported by effective promotions and a comprehensive product range, can drive consumer purchasing decisions during the transition from offline to online shopping.